Konsep Budi Luhur dalam Sapta Darma Ditinjau dari Agama Islam - Wahyudi, Shella Myta; Harahap, Indra (YASIN, 2023)
The Javanese people who live in remote areas are very attached to the term "mystical science" the union between humans living in the world reach Budi Luhur for their perfection in Sapta Darma Budi Luhur as ethics or is a branch of philosophy. Budi Luhur's position is related to respect for the natural world which means relations with fellow human beings and in the hereafter a good relationship with his God. Islam teaches the relevant nobility Al-Akhlaq Al-Karimah. This study aims to analyze the concept of Budi Luhur in Sapta Darma from an Islamic perspective. This study uses a qualitative method, namely by researching a study that is used to collect information and data with the help of various materials in the library such as books, historical stories, and so on with a phenomenological approach using descriptive theory. Based on the author's research that has been carried out and found that nobility in Sapta Darma has an active role in Sapta Darma's belief, namely teaching nobility for the good of all nature and especially humans. Noble vlues that inherit cultural diversity and diverse customs, culture is an adhesive for diversity and noble speech to guide noble attitudes. And the result of the research that can be concluded that Budi Luhur in Sapta Darma and in Islamic teachings is called akhlaq karimah is aimed at making human beings towards glory and has the same definition in a good human behavior in doing good and avoiding evil.